2002
DOI: 10.1046/j.1365-313x.2002.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Position dependent expression of GL2‐type homeobox gene, Roc1: significance for protoderm differentiation and radial pattern formation in early rice embryogenesis

Abstract: SummaryIn early plant embryogenesis, the determination of cell fate in the protodermal cell layer is considered to be the earliest event in radial pattern formation. To elucidate the mechanisms of epidermal cell fate determination and radial pattern formation in early rice embryogenesis, we have isolated a GL2-type homeobox gene Roc1 (Rice outermost cell-speci®c gene1), which is speci®cally expressed in the protoderm (epidermis). In early rice embryogenesis, cell division occurs randomly and the morphologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 39 publications
1
65
0
1
Order By: Relevance
“…These results suggest that SlHDL1 functions in the early stages of the development of the epidermal tissues of anthers and gynoeciums and interacts with genes controlling the formation and function of floral organs. Similar expression patterns have also been reported for the homeodomain-GLABRA2 (HD-GL2) class, in which the homeodomain gene transcript can be detected in the outermost layers of maize (Ingram et al, 1999), rice organs (Ito et al, 2002;Yang et al, 2002), and the shoot apex of Arabidopsis (Lu et al, 1996), as well as for ATHB6, an HD-Zip gene the transcript of which was detected in the epidermis of the developing leaf of Arabidopsis (Soderman et al, 1999).…”
Section: Discussionsupporting
confidence: 58%
“…These results suggest that SlHDL1 functions in the early stages of the development of the epidermal tissues of anthers and gynoeciums and interacts with genes controlling the formation and function of floral organs. Similar expression patterns have also been reported for the homeodomain-GLABRA2 (HD-GL2) class, in which the homeodomain gene transcript can be detected in the outermost layers of maize (Ingram et al, 1999), rice organs (Ito et al, 2002;Yang et al, 2002), and the shoot apex of Arabidopsis (Lu et al, 1996), as well as for ATHB6, an HD-Zip gene the transcript of which was detected in the epidermis of the developing leaf of Arabidopsis (Soderman et al, 1999).…”
Section: Discussionsupporting
confidence: 58%
“…In Arabidopsis, in situ hybridization and/or gene-specific promoter fusions to the GUS reporter gene revealed that nine of the 16 HD-ZIP IV genes show strongly enriched expression in the epidermis, whereas expression of one family member is limited to the subepidermal layer (Rerie et al, 1994;Lu et al, 1996;Masucci et al, 1996;Nakamura et al, 2006;Kubo et al, 2008). Similar results were obtained for all those genes characterized by in situ hybridization in rice (five genes) and maize (five genes; Ingram et al, 1999Ingram et al, , 2000Ito et al, 2002Ito et al, , 2003. Using laser microdissected outer and inner cell layers of juvenile leaves and of the SAM, we obtained layerspecific data for all ZmHDZIV genes but ZmHDZIV11 and ZmHDZIV12.…”
Section: Widespread Epidermal Expression Among Zmhdziv Genesmentioning
confidence: 59%
“…An exhaustive characterization of the 12 remaining Arabidopsis HD-ZIP IV genes by promoter::GUS fusions revealed that the promoters of HOMEODOMAIN GLABRA1 (HDG1), HDG2, HDG5, HDG7, HDG11, and HDG12 direct preferential expression in the epidermal layer of shoot organs (Nakamura et al, 2006). In rice, the five Rice outermost cell-specific genes for which detailed expression data are available are all specifically expressed in the epidermis (Ito et al, 2002(Ito et al, , 2003. Similarly, in maize, four of the five characterized Outer cell layer (OCL) genes (OCL1, OCL3, OCL4, and OCL5) are almost exclusively expressed in the epidermal layer, whereas OCL2 expression is restricted to the subepidermal layer of floral meristems (Ingram et al, 1999(Ingram et al, , 2000.…”
mentioning
confidence: 99%
“…One homoebox gene was recently cloned from the phalaenopsis inflorescence by using degenerate primers based on multiple nucleotide sequence alignment. The homeobox shows homology to the ovulespecific homeobox gene [51] and a rice GL2-type homeobox gene Roc1 specifically expressed in the protoderm or epidermal layer of rice embryo [52]. Stimuli of hormones, such as the auxin-regulated dual specificity cytosolic kinase may induce unusual cell division in the bulge regions of the peloric petals as shown in Fig.…”
Section: Discussionmentioning
confidence: 96%